Relato de experiência na implantação de medição no desenvolvimento de software em uma instituição pública - BEZERRA, Franciellem Mayara Pontes (2020)
An organization that aims to achieve higher productivity and improvement on software development process demands to have quantitative data in hand. This grouped data consists of an information set to assist the analysis of possible strategies to base the required changes in a software organization. Quantitative data can be gathered through the application of the software measurement process. Software measurement is the source of important data to support the decision process for software project management. Thus, this work presents an experience report in the use of software measurement in a public organization, with respect to the planning, gathering and analysis of quantitative data.